ADD C FOR CONTEXT: WHAT CAN LANGUAGE INSTRUCTORS FROM THE HUMANITIES CONTRIBUTE TORESEARCH IN FOREIGN LANGUAGE ACQUISITION? - Dror Abend-David; James Kusch (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2021)
What are some of the challenges and opportunities faced by language instructors who are trained in Literature, Cultural Studies, Film Studies, Philosophy, Translation Studies and other fields in the Humanities? For one thing, such instructors often find themselves outside the theoretical discussion that surrounds their profession. In many cases, language departments rely upon instructors who are trained in disciplines in the humanities to teach FL and SLA courses. We look at previous research in FSLA, as well as CLT and TBLT, to discuss motivation and contextualisation as key factors that determine L2 achievement and attainment. At the heart of the argument is our attempt to teach not only grammar and vocabulary (although we do not, for one minute, pretend that they are unimportant) but also to engage students’ thinking and imagination in relation to language learning. Students enrol in language classes for a number of reasons, and almost all enrol with the ability to think and imagine. The context that we offer in this article is shaped by hermeneutics, phenomenology, literature, media and translation studies. We refer to texts in Literature, Media, and various academic fields both in this article and in class, calling on readers and students to use their imaginations and curiosity to learn more about language and culture. In addition, we supplement the five C’s of the ACTFL - Communication, Culture, Connection, Comparison and Community - with a sixth C for context: the context of global language development through communications, economics, cultural exchange and geographical displacement, exile and immigration.